TELEMEDICINE: REVISITING THE PAST, PRESENT, AND FUTURE DURING COVID PANDEMIC - VISWANATH, KASI; HIREMATH, RAVISHEKAR N; PATEL, PRIYANKA; YADAV, NARENDER; GUPTA, SHIVI; SINGH RANA, TUSHENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Telemedicine is the utilization of electronic facts to correspond expertise for sustaining healthcare when physical distance part the users. Within the same time frame, patient-related data can be simultaneously get collected for large number of people using remote monitoring. However, there is always a disadvantage if any issue arises due to software and hardware. Thus, computer-based patient monitoring can be problematic at sometimes if we exclusively depend on computer system. There should always be a balance between computer dependency and human intelligence use. Each and every one’s life difference can be made by maintaining the balance between the two. Here, in this review article, we discussed the historical perspectives, telemedicine system concepts, telemedicine centers infrastructure, role in diverse spheres, types of telemedicine technology, applications in public health, current initiatives, and finally the success and popularity of telemedicine during COVID-19 pandemic.